The Influence of Digital Content Marketing Fit on Customer Engagement Through Content Engagement in B2B Services - Priambodo Adi Wicaksono; Maria Apsari Sugiat (Interdisciplinary Social Studies, 2025)
In the era of digital transformation, Digital Content Marketing (DCM) has become a key strategy for increasing B2B customer engagement. Telkomsel Enterprise uses various digital platforms to distribute educational content, product promotions, and case studies supporting the customer journey. However, challenges remain in ensuring that content effectively aligns with customer journey stages to maximize engagement and business outcomes. This research aims to analyze the effect of content–customer journey stage fit on content engagement and firm engagement, while testing the mediating role of content engagement and the moderating effects of social media usage frequency and organizational position. This research employed a quantitative approach using scenario-based online experiments. Data were collected from 420 B2B customers of Telkomsel Enterprise who had been exposed to the company's digital marketing content. Analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine direct, mediating, and moderating relationships. Results show that perceived content–journey fit significantly increases content engagement, which fully mediates its effect on firm engagement. Social media usage frequency strengthens the impact of content–journey fit on content engagement, while higher organizational position weakens the effect of content engagement on firm engagement.